2020
DOI: 10.2196/17329
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Paradoxical Relationship of a Creb 3 Regulatory Factor Missense Variant With Body Mass Index and Diabetes Among Samoans: Protocol for the Soifua Manuia (Good Health) Observational Cohort Study

Abstract: Background The prevalence of obesity and diabetes in Samoa, like many other Pacific Island nations, has reached epidemic proportions. Although the etiology of these conditions can be largely attributed to the rapidly changing economic and nutritional environment, a recently identified genetic variant, rs373863828 (CREB 3 regulatory factor, CREBRF: c.1370G>A p.[R457Q]) is associated with increased odds of obesity, but paradoxically, decreased odds of diabetes. Ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…Participants with AA, AG, and GG genotypes were targeted in a 1:2:2 ratio. Protocols for the original GWAS in 2010 and the follow-up study, including genotyping methods, have been previously published [7,8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants with AA, AG, and GG genotypes were targeted in a 1:2:2 ratio. Protocols for the original GWAS in 2010 and the follow-up study, including genotyping methods, have been previously published [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…Eligible participants were not pregnant, lactating, or attempting to control their weight through medication or surgery, were resident on the island of ‘Upolu and were part of a maximally unrelated sample [maximum kinship 6.01%] [8]. Willing participants ( n =519; aged 30.7-72.7 years) gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…All the CREBRF p.Arg457Gln variant carriers, regardless of heterozygote or homozygote, male or female, displayed obviously increased body weight, abdominal circumference, and body length compared with the wild-type littermates. All these phenotypes were resulted from normal diet chow, similar to the human population with the same genotype 19,[21][22][23] . The model is different from obesity linked to diabetes models, such as over-expressing fat mass and obesity-associated (FTO) mice 44 , mice with genetic deletions of melanocortin 4 receptor(MC4R) 45 leptin-de cient mice 46 and zebra sh obesity models 47 , in which the obesity phenotype was primarily caused by increased appetite and food intake and decreased physical activity 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate animal models are necessary to de ne the function of the CREBRF in relation to obesity and mechanisms for protection from T2DM. To date, most studies of CREBRF p.Arg457Gln are limited to the description of phenotypes among speci c human populations [18][19][20][21][22][23][24] . The CREBRF knock-out mice has been used to examine anxiety-like behavior and circulating glucocorticoids in response to various acute stress conditions 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Here we present a secondary, cross-sectional analysis of correlates of CRP in a sample of adult Samoans (ages 35-55 years). Participants were a subsample (n = 108, 50.9% female) of adults who participated in the Soifua Manuia ("Good Health") study of adiposity between 2017 and 2019 (Hawley et al, 2020). The Soifua Manuia study followed up with n = 519 individuals who had participated in a 2010 genome-wide association study that identified a missense variant in the CREBRF gene associated with increased BMI (Minster et al, 2016).…”
Section: Methodsmentioning
confidence: 99%